2024
DOI: 10.1136/jmg-2024-109896
|View full text |Cite
|
Sign up to set email alerts
|

Novel mutation leading to splice donor loss in a conserved site ofDMDgene causes Duchenne muscular dystrophy with cryptorchidism

Jianhai Chen,
Yangying Jia,
Jie Zhong
et al.

Abstract: BackgroundAs one of the most common congenital abnormalities in male births, cryptorchidism has been found to have a polygenic aetiology according to previous studies of common variants. However, little is known about genetic predisposition of rare variants for cryptorchidism, since rare variants have larger effective size on diseases than common variants.MethodsIn this study, a cohort of 115 Chinese probands with cryptorchidism was analysed using whole-genome sequencing, alongside 19 parental controls and 213… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…In recent years, increasing availability of large-scale sequencing of whole exomes and whole genomes have greatly promoted the identification of deleterious variants underlying rare disorders (Richards et al 2015). Statistical and medical studies have demonstrated that rare diseases are often caused by rare variants, which have more significant effects on disease phenotypes than common variants (Richards et al 2015; Wang et al 2021; Chen et al 2022; Greene et al 2023; Jia et al 2023; Weiner et al 2023; Chen et al 2024a). The effect of genebased rare variant burden—the aggregate impact of rare (including de novo germline) protein-altering variants—has been confirmed in many genetic disorders (Purcell et al 2014; Zuk et al 2014; Guo et al 2018; Halvorsen et al 2020; Jiang et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, increasing availability of large-scale sequencing of whole exomes and whole genomes have greatly promoted the identification of deleterious variants underlying rare disorders (Richards et al 2015). Statistical and medical studies have demonstrated that rare diseases are often caused by rare variants, which have more significant effects on disease phenotypes than common variants (Richards et al 2015; Wang et al 2021; Chen et al 2022; Greene et al 2023; Jia et al 2023; Weiner et al 2023; Chen et al 2024a). The effect of genebased rare variant burden—the aggregate impact of rare (including de novo germline) protein-altering variants—has been confirmed in many genetic disorders (Purcell et al 2014; Zuk et al 2014; Guo et al 2018; Halvorsen et al 2020; Jiang et al 2021).…”
Section: Introductionmentioning
confidence: 99%